Intertransverse process block to improve quality of recovery and pain management in cardiac surgery: Protocol for a double-blinded randomized controlled trial - Henry Man Kin Wong; Ranjith Kumar Sivakumar; Wai Tat Wong; Albert Kam Ming Chan; Zion Ho Sum Yeung; Pik Yu Chen; Sherry Tsz Wai Tang; Mandy Hiu Man Chu; Randolph Hung Leung Wong; Kwok Ming Ho (PLoS ONE, 2025)
Background Chronic postsurgical pain (CPSP) after cardiac surgery is significant. Despite the known association between acute pain and CPSP, advanced pain management strategies have not reduced its incidence. Preventing CPSP requires optimizing acute pain control and disrupting central sensitization. The side effects and risks associated with chronic use of current opioid-based cardiac anesthesia necessitate the adoption of multimodal analgesia. Regional anesthesia is a promising alternative, though existing techniques in cardiac surgery have notable limitations. The intertransverse process block (ITPB) is a novel regional technique that offers potential somatic and visceral analgesia. Recent studies demonstrate consistent local anesthetic spread to the intercostal, paravertebral, and epidural spaces, suggesting broader pain control. ITPB may provide a simpler, safer approach in cardiac surgery, reducing the risks of pleural puncture and bleeding. We hypothesize that ITPB will improve quality of recovery, pain control, and health-related quality of life, thereby mitigating chronic postsurgical pain. Methods This is a single-center, randomized, double-blinded, placebo-controlled trial with intention-to-treat analysis. Elective patients awaiting coronary artery bypass grafting, with or without valvular repair or replacement, will be recruited. Ninety-six participants will be randomly assigned to either ITPB or control group. The ITPB group will receive bilateral ITPBs with 20 ml 0.25% levobupivacaine on each side at the T4-5 level under ultrasound guidance, administered before anesthesia induction. Sham blocks, with equal volume of normal saline, will be performed in the control group. The primary outcome is the quality of recovery, assessed using the 15-item Quality of Recovery questionnaire, at 24 hours after tracheal extubation. Secondary outcomes include Numerical Rating Scale pain scores, patient satisfaction, and opioid consumption within 72 hours post-extubation, duration of mechanical ventilation, length of stay in the ICU and hospital, and opioid-related side effects. The incidence of CPSP at 3, 6, and 12 months will be measured, along with pain interference via the Brief Pain Inventory and the Short-Form McGill Questionnaire-2. Discussion Current pain management strategies often rely heavily on opioids, which can have significant side effects and may not adequately address chronic postsurgical pain. This study investigates the efficacy of the intertransverse process block, a novel regional anesthesia technique, in reducing both acute and chronic postsurgical pain in cardiac surgery. Randomized controlled trials on intertransverse process block in cardiac surgery are limited. The results of this study will help define the role of intertransverse process block on the recovery process, and generate vital preliminary data on its potential long-term benefits in reducing chronic postsurgical pain in cardiac surgical population. Clinical trial registration This trial has been prospectively registered at clinicaltrials.gov: NCT06946290